Related Endogenous Retrovirus-K Elements Harbor Distinct Protease Active Site Motifs - Turnbull, Matthew G.; Douville, Renée N. (Frontiers in Microbiology, 2018)
Background: Endogenous retrovirus-K is a group of related genomic elements descending from retroviral infections in human ancestors. HML2 is the clade of these viruses which contains the most intact provirus copies. These elements can be transcribed and translated in healthy and diseased tissues, and some of them produce active retroviral enzymes, such as protease. Retroviral gene products, including protease, contribute to illness in exogenous retroviral infections. There are ongoing efforts to test anti-retroviral regimens against endogenous retroviruses. Herein, we examine the potential activity and diversity of human endogenous retrovirus-K proteases, and their potential for impact on immunity and human disease. Results: Sequences similar to the endogenous retrovirus-K HML2 protease and reverse transcriptase were identified in the human genome, classified by phylogenetic inference and compared to Repbase reference sequences. The topologies of trees inferred from protease and reverse transcriptase sequences were similar and agreed with the classification using reference sequences. Surprisingly, only 62/480 protease sequences identified by BLAST were classified as HML2; the remainder were classified as other HML groups, with the majority (216) classified as HML3. Variation in functionally significant protease motifs was explored, and two major active site variants were identified – the DTGAD variant is common in all groups, but the DTGVD motif appears limited to HML3, HML5, and HML6. Furthermore, distinct RNA expression patterns of protease variants are seen in disease states, such as amyotrophic lateral sclerosis, breast cancer and prostate cancer. Conclusions: Transcribed ERVK proteases exhibit a diversity which could impact immunity and inhibitor-based treatments, and these facets should be considered when designing therapeutic regimens.